Politics in Malaysia the Malay dimension - Gomez, Edmund Terence (Routledge Malaysian studies series, 2007)
Examines various issues in Malaysian politics including human rights, law and democracy, gender and Islam. This book explores the contours of the landscape of Malaysian politics, focusing on politics among the majority ethnic Malay community. It analyzes why transitions have occurred in society yet political parties have not adapted themselves.